The Implementation of The SECI Model in Knowledge Management Adoption Within Local Governments to Foster Innovation - Lesmana Rian Andhika (STI Policy and Management Journal, 2025)
This study examines the application of the SECI model of knowledge management (KM) and how it can contribute to innovation. This study uses a qualitative approach to collect data through semi-structured interviews and case studies. Interviews were conducted with 30 predetermined informants: regional leaders, SPBE (Electronic-Based Government System) managers, and employees involved in planning, implementing, and evaluating innovation (Sumedang and Aceh Tenggara Local Government). This research case study was conducted in the Banyuwangi, Aceh Jaya, and Deli Serdang Local Governments. The results of this study indicate that local governments can improve innovation and public services by creating a learning culture that supports innovation through socialization, externalization, combination, and internalization of knowledge. The recommendations of this study include training and socialization on the importance of knowledge management and creating an environment that supports collaboration. In addition, it is important to involve all stakeholders in the knowledge management planning and implementation process.